Excellent Performance of Earth Dams under Resonance Motion Using Isolator Damping Layer - Behrouz Gordan; Azlan Adnan (Shock and Vibration)
The effect of blanket layer using isolator damping layer (IDL) between river sand foundation and short embankment to remove damage under severe earthquake was investigated in the present study. In case of numerical analysis by ANSYS program, dominant frequency (DF) was computed by free vibration analysis. Soil mechanic tests for thirteen samples to design IDL formula were carried out. In terms of critical condition for earthquake effect such as resonance, five physical small models were tested using vibrator table under the dominant frequency with scale parameter 1/100. As a result, dam was significantly damaged without blanket layer IDL. In order to reduce damage, the best performance was observed using blanket layer (IDL) when this layer was expanded below the reservoir region. The reinforced thickness layer size is one-fourth of dam height. This method is a novel suggestion for earth dam design in seismic zone.